Pendampingan Pia Masa Prapaskah-Paskah Tahun Liturgi C Dengan Metode Ekspresi Berbasis Cerita Anak - Maharani, Fransiska Novia Putri; Hartutik; Yuniarto, Yustinus J. W. (Sekolah Tinggi Katolik Santo Yakobus Merauke, 2022)
PIA mentoring during Lent-Easter Liturgical year C with the method of expression based on children's stories. The purpose of this research is to 1) find out the implementation of Faith Assistance for Children in the Kedu Kevikepan District, 2) find out if the teaching materials for Child Faith Assistance during Lent-Easter Liturgical year C are valid. There is a problem that the PIA mentoring material module is limited. Many assistants do not have a Catholic religious education background and their abilities to facilitate are different. In PIA activities, it is very necessary for mentoring activities such as listening to stories, reading scriptures, games, dancing, singing. Seeing this situation, the researchers used the method of expression with children's stories. This research is a way to find out the teaching materials for PIA mentoring during Lent-Easter Liturgical year C have been valid and suitable to be used in Faith Assistance for Children in the Kedu Kevikepan District. This study uses research and development (R and D) according to Brog and Gall. The technique used is purposive sampling. Taking a sample of 10 people consisting of PIA assistants in the Kedu vikepan, parents, elementary and kindergarten teachers and Catholic religion teachers. Validation is carried out to validate PIA mentoring materials. The validation results obtained an average of 4.6 based on the validation tests carried out. Mentoring materials showed a significant increase in results. The feasibility test for mentoring materials is carried out by conducting FGD (Forum Group Discussion) with valid results and can be used properly and well in the PIA mentoring process in Kedu Kevikepan.